MEASUREMENT OF LINEAR POSITIONAL ERROR AND STRAIGHTNESS ERROR BY LASER INTERFEROMETER - Rusnaldy, Rusnaldy (ROTASI, 2008)
This paper presents the results of measurement of linear positional error and straightness error of a vertical machining center (VMC) using laser interferometer. The laser interferometry tests were performed to measure the linear positional error and straightness error.